Breast cancer after chest irradiation for lymphoma: case report - Fontinele, Danilo Rafael da Silva; Vieira, Sabas Carlos (Mastology, 2020)
Breast cancer is one of the most common diseases among women worldwide. One of the risk factors for the development of this neoplasia is previous radiotherapy on the chest wall. Breast cancer, in turn, is the main long-term concern among women treated for lymphoma with radiation on the chest wall. Thus, we present a case of breast cancer that appeared 18 years after chest radiation for the treatment of lymphoma.